ANALYSIS VALUE CHAIN GOVERNANCE DISTRIBUTION CHANNEL OF VANNAMEI SHRIMP FARMERS IN MRANDUNG BANGKALAN - Silvia Eri; Yudhi Prasetya Mada (Jurnal Kajian Ilmu Manajemen (JKIM), 2021)
The people of Mrandung has plunged into of business shrimp farmer, mostly the type of shrimp chosen is vannamei shrimp ( Litopenaeus vannamei ), the aim of this study is to find out and to analysis of the distribution channel governance chain value in Mrandung, the method that used in this study is a qualitative research, and the conclusion in this study is that indigenous people lack of knowledge in governance and the value chain of the vannamei shrimp distribution channel so that many farmers suffer losses due to unknowledgeable. But on the other hand there is a company namely PT. TBAI (Tanjung Bumi Indonesian Aquaculture) that engaged in vannamei shrimp farming and the company has been already using good corporate governance and the distribution channel value chain, making it is quite maximum for the company's value. The results of this study show governance on company farms vannamei shrimp was very good, the value chain of distribution channels has been using are already managed well with using three distribution channels more widely, while the governance from distribution channels chain vannamei shrimp farmer I use two distribution channels more simple than others and shrimp vannamei farmer II uses one distribution channel chain more complexly than I.